HEALTH PROMOTION WITH SOY MILK IN OVERCOMING COMPLAINTS IN PRE MENOPOUSE - Nikmah Jalilah Ritonga; Diah Evawanna; Riris Sitorus; Dwi Handayani (JURNAL PENGMAS KESTRA (JPK), 2022)
Pre menopause is a physiological condition characterized by irregular menstruation. Symptoms that often arise include hot flushes, night sweats, restlessness, fatigue, pain during intercourse. Based on recent research that non-pharmacological treatment of pre-menopausal complaints can be done with soy milk. Health promotion activities through the provision of soy milk can be used as an alternative to prevent and treat cases of pre-menopausal symptoms. The purpose of this community service is to improve the quality of life of women who enter menopause through efforts to prevent and treat symptoms that arise through non-pharmacological efforts. Soy milk is given every day in the morning for 1 week regularly. The implementation of this community service lasted for 8 days in the Bandar Khalipah Health Center Work Area, Percut Sei Tuan Deli Serdang District. This activity was initiated through a Rapid Test examination then followed by measuring the complaints of pre-menopausal symptoms felt by respondents using the MRS questionnaire, then continued with giving soy milk for 1 hour. weeks. On day 8, all respondents were again measured for premenopausal symptoms using the MRS questionnaire. The results of measuring premenopausal symptoms after giving soy milk for 1 week showed that there was a decrease in complaints of menopausal symptoms felt by respondents after consuming soy milk for 1 week on a regular basis by 66.7% who experienced mild complaints and 33.3% experienced moderate complaints. Giving soy milk can be useful in overcoming premenopausal symptoms.